Electromechanical Assessment of Human Knee Articular Cartilage with Compression-Induced Streaming Potentials. (January 2016) - Becher, Christoph; Ricklefs, Marcel; Willbold, Elmar; Hurschler, Christof; Abedian, Reza
Purpose: To assess the electromechanical properties of human knee articular cartilage with compression-induced streaming potentials for reliability among users and correlation with macroscopic and histological evaluation tools and sulfated glycosaminoglycan (sGAG) content. Methods: Streaming potentials are induced in cartilage in response to loading when mobile positive ions in the interstitial fluid temporarily move away from negatively charged proteoglycans. Streaming potential integrals (SPIs) were measured with an indentation probe on femoral condyles of 10 human knee specimens according to a standardized location scheme. Interobserver reliability was measured using an interclass correlation coefficient (ICC). The learning curves of 3 observers were evaluated by regression analysis. At each SPI measurement location the degradation level of the tissue was determined by means of the International Cartilage Repair Society (ICRS) score, Mankin score, and sGAG content. Results: The computed ICC was 0.77 (0.70-0.83) indicating good to excellent linear agreement of SPI values among the 3 users. A significant positive linear correlation of the learning index values was observed for 2 of the 3 users. Statistically significant negative correlations between SPI and both ICRS and Mankin scores were observed ( r = 0.502, P < 0.001, and r = 0.255, P = 0.02, respectively). No correlation was observed between SPI and sGAG content ( r = 0.004, P = 0.973). Conclusions: SPI values may be used as a quantitative means of cartilage evaluation with sufficient reliability among users. Due to the significant learning curve, adequate training should be absolved before routine use of the technique.